The syntax and semantics of approximate indefi nites in Spanish - Carranza, Fernando Martín; Pérez, Carlos Muñoz (DELTA: Documentação e Estudos em Linguística Teórica e Aplicada, 2021)
In Spanish, combining an indefi nite plural article and a cardinal number leads to an approximative interpretation similar to that provided by approximators like ‘approximately’. In this paper, we advance a syntactic and semantic analysis of these structures. We show that the construction shares a number of properties with structures containing explicit approximative elements, so it justifi ed to assume that a particular constituent contributes the approximative meaning. We propose that an approximative morpheme APPROX is combined with the cardinal number; the morphological realization of this morpheme is as the plural affi x on the indefi nite article. We advance a denotation for APPROX, and elaborate the necessary assumptions on the functioning of numerals for our analysis to work at a general level.